Natural language explanation of SQL queries for database education - Pow, Liang Hong (Nanyang Technological University, 2022)
Data exists everywhere around us. However, despite the rise in dependency on relational databases, there still exists a fundamental limitation to being able to fetch data from them. This is because users are first required to comprehend convoluted structured query languages. As a result, there exist plenty of means to translate natural language to structured query languages. By contrast, there exists little research done in the opposite direction, from structured query language to natural language. This will be essential to aid users in understanding already written queries. To the best of my knowledge, this work is the first to focus on translating structured query language to natural language. This body of work presents an interface that allows users to perform translations from structured query language to natural language as opposed to the conventional natural language to structured query language translation. This helps users understand what each query does.